Augmented Reality Media As A Butterfly Metamorphosis Learning Method Based Marker Tracking: Augmented Reality Media As A Butterfly Metamorphosis Learning Method Based Marker Tracking - Muhammad Prabowo Chaniago; Agung Triayudi; Endah Tri Esthi (Jurnal Mantik, 2020)
This study specifically the butterfly metamorphosis of learning can be done with various media for users of grades 4 through 5 elementary schools and must be attenuated by the instructor in the learning process. This study uses a marker-based search method to help study the butterfly metamorphosis in 3D on a smartphone registered devices. Augmented Reality Also has a Rapid Angle Detection algorithm to support a marker object in it. In the results and application testing colors are not suitable for the visualization process while it is still a perspective that can be processed by the Angle Rapid Detection algorithm and 0-20% in light testing can not be used 21-40% of long Appears 41- 100% faster Appearsr,